E6 and E7 from Human Papillomavirus Type 16 Cooperate To Target the PDZ Protein Na/H Exchange Regulatory Factor 1 - Accardi, Rosita (American Society for Microbiology, 2011)

(untitled)
Previous studies have shown that the PDZ-binding motif of the E6 oncoprotein from the mucosal high-risk (HR) human papillomavirus (HPV) types plays a key role in HPV-mediated cellular transformation in in vitro and in vivo experimental models. HR HPV E6 oncoproteins have the ability to efficiently degrade members of the PDZ motif-containing membrane-associated guanylate kinase (MAGUK) family; however, it is possible that other PDZ proteins are also targeted by E6. Here, we describe a novel interaction of HPV type 16 (HPV16) E6 with a PDZ protein, Na(+)/H(+) exchange regulatory factor 1 (NHERF-1), which is involved in a number of cellular processes, including signaling and transformation. HPV16 E6 associates with and promotes the degradation of NHERF-1, and this property is dependent on the C-terminal PDZ-binding motif of E6. Interestingly, HPV16 E7, via the activation of the cyclin-dependent kinase complexes, promoted the accumulation of a phosphorylated form of NHERF-1, which is preferentially targeted by E6. Thus, both oncoproteins appear to cooperate in targeting NHERF-1. Notably, HPV18 E6 is not able to induce NHERF-1 degradation, indicating that this property is not shared with E6 from all HR HPV types. Downregulation of NHERF-1 protein levels was also observed in HPV16-positive cervical cancer-derived cell lines, such as SiHa and CaSki, as well as HPV16-positive cervical intraepithelial neoplasia (CIN). Finally, our data show that HPV16-mediated NHERF-1 degradation correlates with the activation of the phosphatidylinositol-3′-OH kinase (PI3K)/AKT signaling pathway, which is known to play a key role in carcinogenesis.